2016
DOI: 10.1097/md.0000000000003263
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Factors Affecting Emergency Department Length of Stay—Using a Competing Risk-accelerated Failure Time Model

Abstract: Emergency department (ED) length of stay (LOS) is associated with ED crowding and related complications. Previous studies either analyzed single patient disposition groups or combined different endpoints as a whole. The aim of this study is to evaluate different effects of relevant factors affecting ED LOS among different patient disposition groups.This is a retrospective electronic data analysis. The ED LOS and relevant covariates of all patients between January 2013 and December 2013 were collected. A compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 38 publications
6
42
1
Order By: Relevance
“…In two other studies, one using the Australian Triage System and one using the Canadian Triage Acuity System, a longer ED LOS was found in higher acuity patients [2022]. Besides triage acuity level, advanced age has also been found to be related to a longer LOS among discharged patients [19, 23, 24]. In our study, after controlling for the effect of disease acuity, exams, or whether a consultation was provided, the effect of age group still showed a significant trend in time ratios.…”
Section: Discussionmentioning
confidence: 99%
“…In two other studies, one using the Australian Triage System and one using the Canadian Triage Acuity System, a longer ED LOS was found in higher acuity patients [2022]. Besides triage acuity level, advanced age has also been found to be related to a longer LOS among discharged patients [19, 23, 24]. In our study, after controlling for the effect of disease acuity, exams, or whether a consultation was provided, the effect of age group still showed a significant trend in time ratios.…”
Section: Discussionmentioning
confidence: 99%
“…These results same with the study that explained that there was significant difference in the AVLOS that was found between inpatient (Mean = 544 minutes, SD = 323 minutes) and outpatient (mean = 291 minutes, SD = 286 minutes). This proven that if ED carry out more discharged inpatient compared with outpatients, it would lengthened the LOS of patients in the ED (Chaou et al, 2016).…”
Section: Correlation Between Patients Discharge Type With Losmentioning
confidence: 95%
“…patients who are transferred in intensive care. Among the three types of patients discharge type from the ED and their correlation factor for each of them are not same (Chaou et al, 2016).…”
mentioning
confidence: 96%
“…those with higher acuity, (Chaou et al, 2016) and those with specific histories including hypertension or atrial fibrillation (Rashid et al, 2013) show longer length of stay. Other barriers to throughput include delayed consultant input (Hosseininejad et al, 2017) or diagnostic tests (Yoon et al, 2003).…”
Section: Emergency Department Length Of Staymentioning
confidence: 99%